Pembuatan Bibliografi Beranotasi Koleksi Minangkabausiana di UPT Perpustakaan Proklamator Bung Hatta Bukittinggi - Putri, Debby; Marlini, Marlini (Ilmu Informasi Perpustakaan dan Kearsipan, 2016)
Writing in this paper on the production of the Annotated Bibliography in UPT Library of Bung Hatta Bukittinggi. This study aims to help users and librarians in making information retrieval using a means of controlling the form of a bibliography. The purpose of writing annotated bibliographies describe the making of the collection Minangkabausiana especially books on UPT Library of Bung Hatta Bukittinggi.Writing this paper uses descriptive method. Data obtained from the collection directly, which is looking for the physical form in the library collection. The object of research is a collection of Minangkabau in book form approximately 92 titles.Penganalisasian Based on the data, it was concluded the following matters. (1) determination of the title bibliography, this bibliography entitled Annotated Bibliography Collection Minangkabausiana in UPT Library of Bung Hatta Bukittinggi; (2) the collection of library materials or information retrieval, which is done by the direct search; (3) the selection of library materials, aims to determine the theme of the book that will be made is the theme Minangkabausiana bibliographies; (4) the classification or classifications, which this bibliography aims to describe the subject matter in the book; (5) the keyword generation, aims to describe the subject matter in the book; (6) index, which index is taken from the author index, subject index, subject index; (7) production or manuscript typing bibliographies, should be in accordance with predetermined rules; (8) checks the final manuscript bibliography, in the form of written examination of errors in spelling and punctuation, suitability shortening and reversal of the author's name.Keyword: Bibliography, Minangkabau, anotasi, Indeks.